2014
DOI: 10.1021/jf5041614
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Imidacloprid Insecticide by Ag-Deposited Titanate Nanotubes: A Study of Intermediates and Their Reaction Pathways

Abstract: The present work demonstrates the influence of Ag-loading (0.2-1.0 wt %) onto sodium titanate nanotubes (TNT) for complete photomineralization of the neurotoxic imidacloprid (IMI) insecticide under UV light illumination. It has been observed that degradation of IMI follows pseudo-first-order kinetics, where 0.5 wt % Ag-loaded TNT exhibited highest apparent rate constant (2.2 × 10(-2) min(-1)) and corresponding least half-life (t1/2) of 31 min for IMI relative to bare P25-TiO2 (3.4 × 10(-3) min(-1), t1/2 = 230 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…It is well known that the photo‐Fenton method, combined with Fenton's reagent and UV or visible light, is a common method for imidacloprid removal in water . Different types of heterogeneous catalysts like TiO 2 /UV‐A, Fe/TiO 2 and Ag/TNT have been reported to be effective in the removal of imidacloprid or some other harmful organic compounds . However, there were few reports on the photocatalytic degradation of imidacloprid by Ag/AgBr under visible light.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the photo‐Fenton method, combined with Fenton's reagent and UV or visible light, is a common method for imidacloprid removal in water . Different types of heterogeneous catalysts like TiO 2 /UV‐A, Fe/TiO 2 and Ag/TNT have been reported to be effective in the removal of imidacloprid or some other harmful organic compounds . However, there were few reports on the photocatalytic degradation of imidacloprid by Ag/AgBr under visible light.…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that the 2‐nitroiminoimidazolidine group plays a key role in the mechanism of its insecticidal activity, 14 although some authors also emphasize the role of the chlorine atom of the pyridyl group in insecticidal activity and resistivity 15 . Under natural conditions, the mineralization of imidacloprid is incomplete because it oxidizes to other heteroatom‐containing intermediates that are sometimes even more toxic and persistent than imidacloprid 16 . A recent study has shown that imidacloprid has a stronger chronic toxicity than clothianidin and thiamethoxam, causing a greater than additive negative effect due to interaction with mentioned neonicotinoids 17 …”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, heterogeneous photocatalysis has proven to be an efficient, environmentally friendly and cost‐effective technique for reducing the concentration of various pollutants in water media. This also applies to the photocatalytic degradation of imidacloprid, which has been investigated using various photocatalysts, mainly TiO 2 ‐P25 and modified TiO 2 , 10,18,19 as well as hybrid and composite photocatalysts such as Ag/TNT, 16 H 3 PW 12 O 40 /La‐TiO 2 , 20 GO/Fe 3 O 4 /TiO 2 ‐NiO, 21 g‐C 3 N 4 /ZnO, 22 Bi 2 WO 6 /NH 2 ‐MIL‐88B(Fe), 23 etc. In order to improve the photocatalytic performance of the most researched TiO 2 and to extend the photocatalytic activity of TiO 2 towards longer wavelengths (visible light), various strategies have been developed, such as morphological modification (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre os metais utilizados na modificação de óxidos à base de TiO2, a prata se destaca pela versatilidade de aplicações, contribuindo para a atividade fotocatalítica (Guo et al, 2009;Grover et al, 2014), ação bactericida (Grandcolas et al, 2011), fotocromismo (Miao et al, 2007) e captura de Iradioativo (Yang et al, 2013). Apesar de ser um metal nobre com alto potencial de redução, o cátion Ag + forma compostos estáveis que tornam a manipulação dos reagentes bastante fácil em comparação com outros metais nobres.…”
Section: Tnss Modificadas Com Agunclassified